Հայաստանի ուշմիջնադարյան (15-18-րդ դարեր) տապանաքարային պատկերաքանդակի պատճառաբանական, պատկերագրական և իմաստաբանական քննության փորձ - Պետրոսյան, Համլետ Լ. («Նաիրի» հրատ.)
The article presents the reasons of emergence and circumstances of functioning, typology and chronology of tombstones in late medieval Armenia. The origins, main themes and characters of human and animal figurative reliefs are discussed in detail with semantic and symbolic aspects.
Keywords: Տապանաքարեր; Միջնադարյան հայ մշակույթ